Study of a Newtonian Fluid through Circular Channels with Slip Boundary Taking into Account Electrokinetic Effect - Sun, Qian; Wu, Yong Hong; Liu, Lishan; Wiwatanapataphee, B (Hindawi Publishing Corporation, 2013)
We study the slip flow of fluids driven by the combined effect of electrical force and pressure gradient. The underlying boundary value problem is solved through the use of Fourier series expansion in time and Bessel function in space. The exact solutions and numerical investigations show that the slip length and electrical field parameters have significant effects on the velocity profile. By varying these system parameters, one can achieve smooth velocity profiles or wave form profiles with different wave amplitude and frequency. This opens the way for optimizing the flow by choosing the slip length, the electrical field, and electrolyte solutions.